Belgium : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2002 Article IV Consultation highlights that Belgium's real GDP growth fell sharply in 2001 to 0.8 percent and remained weak in 2002 at an estimated 0.7 percent. The fundamental factor behind these developments was the slowdown in the economies of Belgium's trading partners, especially Germany. Thus, Belgium's export market growth fell from a robust 12.1 percent in 2000 to only 0.6 percent in 2001; in 2002, export markets shrank an estimated 1 percent. In 2002, employment began to decline and unemployment began to rise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet